Early Devotion to Jesus: A Report, Reflections and Implications - Hurtado, Larry W. (The expository times, 2011)
Over the last 20+ years there has been a renewed interest in earliest expressions of devotion to Jesus as a historical phenomenon. Research of these years has underscored how early Jesus-devotion emerged within the first years of the Christian movement and among circles of Jewish believers. The resultant devotional pattern, involving two distinguishable figures (God and Jesus), comprises a remarkable development, thus, in ancient Jewish monotheistic religion. This development is most noteworthy in the way that Jesus functions in the corporate worship life of early Christian circles. This essay reports on some of this recent research and the main findings.